Implementasi Pendidikan Karakter Melalui Media Film dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Cempa Kabupaten Pinrang - Ridwan Haer (IAIN PAREPARE, 2018)
ABSTRACTThis paper is about the Implementation of Character Education through FilmMedia in Learning Islamic Education in SMP Negeri 1 Cempa, Pinrang Regency.The purpose of this study is to describe the planning, implementation, and impactof the implementation of character education through film media in the learningprocess of Islamic Education in SMP Negeri 1 Cempa, Pinrang Regency.This research is a qualitative research with a naturalistic paradigm. Theinstruments used in this study are: observation guidelines, interview guidelines,and researchers as key instruments. The informants interviewed in this study wereprincipals, deputy heads of curriculum, Islamic Education teachers, and students.The results showed that the planning of character education using the film SunanKalijaga in the learning process of Islamic Education was done by planning in theform of a Learning Implementation Plan (RPP) supervised by the school, reviewingthe media, and reviewing learning material. The implementation of charactereducation is done by integrating character values into the material of IslamicEducation, especially related to moral material using the film Sunan Kalijaga thatis applied using the inquiry method. The implementation of character educationthrough film media in the learning of Islamic Education has an impact inimproving the quality of learning that is more fun, motivating, inspiring, andmeaningful. In addition, students are inspired to live up to character values such ascaring, courtesy and honesty to be applied in daily interactions.